Low-cost high-specific-energy iron-manganese-based sodium-ion battery positive electrode material as well as preparation method and application thereof
By adjusting the element ratio and preparation process of the iron-manganese-based positive electrode material with chemical formula NaaFebMncNixCuyMgzTiwO2, the problem of poor circulation performance of the iron-manganese-based positive electrode material in the prior art is solved, and the compatibility effect of high energy density and good cycle stability is achieved.
Patent Information
- Application Number
- CN202411882602.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
The lack of iron-manganese-based positive electrode materials with high energy density, good long cycle performance and reasonable first-term effects in the prior art limits the practical application of sodium ion batteries.
The chemical formula of NaaFebMncNixCuyMgzTiwO2 is used to improve the circulation stability and energy density of the material by adjusting the element ratio and preparation process.
It achieves low cost, high energy density, good cycle stability and first-time charge and discharge capacity close to balance, improving the practicality of iron-manganese-based materials.
Smart Images

Figure CN119695141A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material, a preparation method and application thereof. Background Art
[0002] Reducing the nickel content in layered oxides is an important measure to give full play to the cost advantage of sodium-ion batteries. The development of layered oxides for sodium-ion batteries composed of low-cost metals is of great significance. Among many transition metal elements, iron and manganese have the lowest cost and can provide considerable capacity. Therefore, the research on low-cost and high-energy iron-manganese-based sodium-ion battery positive electrode materials will help improve the cost-effectiveness and market competitiveness of sodium-ion batteries. Yabuuchi et al. first synthesized a FeMn-based positive electrode material with a P2-type structure. 3+ / Fe 4+ and Mn 3+ / Mn 4+ The redox pair, P2-Na 2 / 3 [Fe 1 / 2Mn 1 / 2 ]O2 showed 190mA hg -1 The high reversible capacity of P2-Na 2 / 3 [Fe 1 / 2 Mn 1 / 2 ]The first discharge capacity of O2 is much larger than its first charge capacity, making it difficult to use in full batteries.
[0003] The existing technology has obtained some iron-manganese-based materials with high reversible capacity, but their long-cycle stability is still poor, and their high initial efficiency also restricts practical applications. Therefore, it is an urgent task for current research to develop iron-manganese-based positive electrode materials with high energy density, good long-cycle performance and reasonable initial efficiency. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a low-cost, high-specific-energy iron-manganese-based sodium ion battery positive electrode material and a preparation method and application thereof, so as to solve the problem in the prior art of lack of iron-manganese-based positive electrode materials with high energy density, good long cycle performance and reasonable first effect.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: Provide a low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material, the chemical formula of which is Na a Fe b Mn c Ni x Cu y Mg z Ti wO2, wherein b+c+x+y+z+w=1, 0.6≤a≤0.7, 0<x≤0.1, 0<y≤0.1, 0<z≤0.1, 0<w≤0.1; a is the sodium content, and b, c, x, y, z, w are the contents of the corresponding elements.
[0006] On the basis of the above technical solution, the present invention can also be improved as follows:
[0007] Further, the chemical formula is: Na 0.65 Fe 0.35 Mn 0.45 Ni 0.05 Cu 0.05 Mg 0.05 Ti 0.05 O2.
[0008] Further, the chemical formula is: Na 0.63 Fe 0.39 Mn 0.45 Ni 0.04 Cu 0.04 Mg 0.04 Ti 0.04 O2 or Na 0.67 Fe 0.31 Mn 0.45 Ni 0.06 Cu 0.06 Mg 0.06 Ti 0.06 O2.
[0009] The present invention also provides a method for preparing the above-mentioned low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material, comprising the following steps:
[0010] (1) weighing sodium carbonate, ferric oxide, manganese dioxide, nickel oxide, copper oxide, magnesium oxide and titanium dioxide according to the ratio of each element in the chemical formula to obtain raw material powders, mixing them evenly, and drying them to obtain a mixed powder;
[0011] (2) The mixed powder obtained in step (1) is tableted, calcined, cooled to room temperature, and ground into powder to obtain a low-cost, high-energy-density iron-manganese-based sodium ion battery positive electrode material.
[0012] Furthermore, in step (1), the molar amount of sodium carbonate weighed is 2% in excess.
[0013] Furthermore, in step (1), ball milling is used for mixing, the ball milling medium is ethanol, the ball milling speed is 300-400 r / min, and the ball milling time is 4-6 h.
[0014] Furthermore, the ball milling medium is 3-5 wt % of the raw material powder.
[0015] Furthermore, in step (1), the mixture is dried at 75-85°C.
[0016] Furthermore, in step (2), tableting is performed at 16-18 MPa.
[0017] Furthermore, in step (2), calcination is performed at 900-1000° C. for 10-15 hours.
[0018] Furthermore, the heating rate during calcination is 3-8°C / min.
[0019] The present invention also provides the use of the above-mentioned low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material in the preparation of sodium ion batteries.
[0020] The present invention has the following beneficial effects:
[0021] 1. The battery positive electrode material of the present invention has low cost, high energy density, good cycle stability and coulombic efficiency close to equilibrium in the first charge and discharge. The present invention increases the valence state of manganese in the iron-manganese-based positive electrode material by replacing low-valent ions (divalent nickel and divalent copper), reduces the Jan-Taylor effect, and thus improves the long-cycle stability; and the low-valent ions can provide capacity, which is conducive to balancing the first charge and discharge capacity, thereby reducing the first efficiency. In addition, non-electrochemically active ions (divalent magnesium and tetravalent titanium) alleviate large volume phase changes and further improve cycle stability.
[0022] 2. The present invention adopts Ni 2+ , Cu 2+ Mg 2+ and Ti 4+ The replacement helps to improve the long-cycle stability and Coulomb efficiency, greatly enhancing the practicality of iron-manganese-based materials.
[0023] 3. Take Na 0.65 Fe 0.35 Mn 0.45 Ni 0.05 Cu 0.05 Mg 0.05 Ti 0.05 Taking O2 as an example, in terms of cost, transition metal elements account for 80%, which are low-cost Fe and Mn elements. Compared with nickel-manganese-based materials such as Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2, the iron-manganese-based Na 0.65 Fe 0.35 Mn 0.45 Ni 0.05 Cu 0.05 Mg 0.05 Ti 0.05The Ni content used in O2 is greatly reduced, so it has a lower cost; in terms of specific energy: the sodium ion half-battery assembled based on the positive electrode material of the present invention has a high specific capacity (the specific capacity at 0.1C is 147mAh·g -1 ) and a higher average operating voltage (3.07V), thus having a high specific energy (discharge specific energy of 451Wh·kg -1 ); Cycle performance: The sodium ion half-battery assembled based on the cathode material of the present invention has good cycle stability (the capacity retention rate is 84.8% after 150 cycles at 1C), achieving compatibility between high specific energy and long cycle; First cycle coulombic efficiency: Compared with the original P2-Na 0.67 Fe 1 / 2 Mn 1 / 2 O2 material (first cycle coulombic efficiency 144%), the first charge and discharge capacity of the positive electrode material of the present invention is more balanced (first cycle coulombic efficiency 124%). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD spectrum of the positive electrode material of Example 1.
[0025] Figure 2 This is the XRD spectrum of the positive electrode material of Comparative Example 1.
[0026] Figure 3 This is a charge and discharge curve diagram of the sodium ion battery of Example 1.
[0027] Figure 4 This is a charge and discharge curve diagram of the sodium ion battery of Comparative Example 1.
[0028] Figure 5 This is a test curve diagram of the cycle performance of the sodium ion battery of Example 1.
[0029] Figure 6 This is a test curve of the cycle performance of the sodium ion battery of Comparative Example 1. DETAILED DESCRIPTION
[0030] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] Embodiment 1:
[0032] A low-cost and high-energy iron-manganese-based sodium-ion battery cathode material (Na 0.65 Fe 0.35 Mn 0.45 Ni 0.05 Cu0.05 Mg 0.0 5Ti 0.05 O2), the preparation method thereof comprises the following steps:
[0033] (1) According to the ratio of each element in the chemical formula, 9.945 mmol sodium carbonate (2% excess), 5.25 mmol ferric oxide, 13.5 mmol manganese dioxide, 1.5 mmol nickel oxide, 1.5 mmol copper oxide, 1.5 mmol magnesium oxide and 1.5 mmol titanium dioxide are accurately weighed to obtain raw material powder, which is placed in an agate ball mill, and 4 wt% of anhydrous ethanol is added as a wet grinding medium. The raw material powder is ball milled at a speed of 320 rpm for 5 h. After being mixed evenly, it is dried in an oven at 80° C. to obtain a mixed powder;
[0034] (2) The mixed powder obtained in step (1) is pressed into a disc with a diameter of 12 mm using a tablet press at 18 MPa, and placed in a muffle furnace at a heating rate of 5° C. / min, calcined at 900° C. for 15 h, cooled naturally to room temperature, and ground into powder to obtain a low-cost, high-energy iron-manganese-based sodium ion battery positive electrode material.
[0035] A sodium ion half-cell, the preparation method of which comprises the following steps:
[0036] S1: Weigh the low-cost, high-energy-density iron-manganese-based sodium ion battery positive electrode material, conductive additive (Super P) and binder (PVDF) prepared in step (2) according to a mass ratio of 7.5:1.5:1, add an appropriate amount of solvent N-methylpyrrolidone (NMP), stir evenly to obtain a positive electrode slurry, use a scraper to evenly coat it on an aluminum foil, place it in a blast oven, dry it until NMP is completely volatilized, then place it in a vacuum oven at 80°C, dry it for 10 hours, and punch it into a positive electrode sheet with a diameter of 10 mm;
[0037] S2: The positive electrode sheet and the metal sodium sheet negative electrode with a diameter of 12 mm were assembled into a sodium ion battery. The electrolyte consisted of 1 mol / L NaClO4 and propylene carbonate (PC) with 5 wt% fluoroethylene carbonate (FEC) added. The separator was a glass fiber membrane with a diameter of 16 mm (GF / D, Whatman). CR2032 button cells were assembled in a glove box with an argon atmosphere.
[0038] Embodiment 2:
[0039] A low-cost and high-energy iron-manganese-based sodium-ion battery cathode material (Na 0.63 Fe 0.39 Mn 0.45 Ni 0.04 Cu 0.04 Mg 0.0 4Ti 0.04O2), the preparation method thereof comprises the following steps:
[0040] (1) According to the ratio of each element in the chemical formula, 9.639 mmol sodium carbonate (2% excess), 5.85 mmol ferric oxide, 13.5 mmol manganese dioxide, 1.2 mmol nickel oxide, 1.2 mmol copper oxide, 1.2 mmol magnesium oxide and 1.2 mmol titanium dioxide were accurately weighed to obtain raw material powder, which was placed in an agate ball mill, and 3 wt% anhydrous ethanol was added as a wet grinding medium. The raw material powder was ball milled at a speed of 300 rpm for 6 h. After being mixed evenly, the raw material powder was dried in an oven at 75° C. to obtain a mixed powder.
[0041] (2) The mixed powder obtained in step (1) is pressed into a disc with a diameter of 12 mm using a tablet press at 16 MPa, and placed in a muffle furnace at a heating rate of 3° C. / min, calcined at 800° C. for 12 h, cooled naturally to room temperature, and ground into powder to obtain a low-cost, high-energy iron-manganese-based sodium ion battery positive electrode material.
[0042] A sodium ion half-cell, the preparation method of which comprises the following steps:
[0043] The above-mentioned battery positive electrode material is used, and the rest is the same as in Example 1.
[0044] Embodiment 3:
[0045] A low-cost and high-energy iron-manganese-based sodium-ion battery cathode material (Na 0.67 Fe 0.31 Mn 0.45 Ni 0.06 Cu 0.06 Mg 0.0 6Ti 0.06 O2), the preparation method thereof comprises the following steps:
[0046] (1) According to the ratio of each element in the chemical formula, 10.251 mmol sodium carbonate (2% excess), 4.65 mmol ferric oxide, 13.5 mmol manganese dioxide, 1.8 mmol nickel oxide, 1.8 mmol copper oxide, 1.8 mmol magnesium oxide and 1.8 mmol titanium dioxide were accurately weighed to obtain raw material powder, which was placed in an agate ball mill, and 5 wt% anhydrous ethanol was added as a wet grinding medium. The raw material powder was ball milled at 400 rpm for 4 h. After being mixed evenly, the raw material powder was dried in an oven at 85° C. to obtain a mixed powder.
[0047] (2) The mixed powder obtained in step (1) is pressed into a disc with a diameter of 12 mm using a tablet press at 17 MPa, and placed in a muffle furnace at a heating rate of 8° C. / min, calcined at 1000° C. for 10 h, naturally cooled to room temperature, and ground into powder to obtain a low-cost, high-energy iron-manganese-based sodium ion battery positive electrode material.
[0048] A sodium ion half-cell, the preparation method of which comprises the following steps:
[0049] The above-mentioned battery positive electrode material is used, and the rest is the same as in Example 1.
[0050] Comparative Example 1:
[0051] An iron-manganese-based sodium ion battery positive electrode material (Na 0.67 Fe 0.5 Mn 0.5 O2), and its preparation method comprises the following steps:
[0052] Accurately weigh 10.251 mmol of sodium carbonate (2% excess), 7.5 mmol of ferric oxide and 7.5 mmol of manganese oxide, and the rest is the same as in Example 1.
[0053] A sodium ion half-cell, the preparation method of which comprises the following steps:
[0054] The raw material used is the above-mentioned iron-manganese-based sodium ion battery positive electrode material, and the rest is the same as Example 1.
[0055] Test example
[0056] 1. The battery positive electrode materials prepared in Example 1 and Comparative Example 1 were tested by XRD spectra, and the results are shown in Figure 1-2 .
[0057] Depend on Figure 1 It can be seen that the majority of the positive electrode material obtained in Example 1 is of P2 structure, and a small amount is of O3 structure.
[0058] Depend on Figure 2 It can be seen that the positive electrode material obtained in Comparative Example 1 is a P2 structure.
[0059] 2. The sodium ion half-cells prepared in Example 1 and Comparative Example 1 were subjected to constant current charge and discharge curve performance tests in the test voltage range of 2-4.2V. The constant current charge and discharge curves were measured at 0.1C (1C = 150 mA g -1 ) under the first three cycles of charge and discharge curves, the results are shown in Figure 3-4 .
[0060] Depend on Figure 3 It can be seen that the first cycle discharge capacity of the sodium ion battery prepared in Example 1 is 147 mAh g -1 , the first-cycle Coulomb efficiency is 124%;
[0061] Depend on Figure 4 It can be seen that the first cycle discharge capacity of the sodium ion battery prepared in Comparative Example 1 is 158 mAh g -1 , the first-cycle Coulomb efficiency is 144%.
[0062] 3. The sodium ion half-cells prepared in Example 1 and Comparative Example 1 were subjected to constant current charge and discharge curve performance tests in the test voltage range of 2-4.2V. The test was performed at a 1C rate (150mA·g -1 ) for 150 cycles. Figure 5-6 .
[0063] Depend on Figure 5 It can be seen that the capacity of the sodium ion battery prepared in Example 1 at 1C rate is 112 mAh g -1 ; The capacity retention rate is 84.8%, showing good cycle stability.
[0064] Depend on Figure 6 It can be seen that the capacity of the sodium ion battery prepared in Comparative Example 1 at 1C rate is 109 mAh g -1 ; The capacity retention rate is 33.4%, and the cycle stability is poor.
[0065] The above test results are shown in Table 1.
[0066] Table 1
[0067]
[0068] It can be seen from Table 1 that the material proposed in the present invention greatly improves the cycle stability while maintaining a high specific energy, and the first-cycle coulombic efficiency is more balanced.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-cost, high-energy iron-manganese-based sodium ion battery positive electrode material, characterized in that: The chemical formula is Na a Fe b Mn c Ni x Cu y Mg z Ti w O2, wherein b+c+x+y+z+w=1, 0.6≤a≤0.7, 0<x≤0.1, 0<y≤0.1, 0<z≤0.1, 0<w≤0.1; a is the sodium content, and b, c, x, y, z, w are the contents of the corresponding elements.
2. The low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 1, characterized in that: The chemical formula is: Na 0.65 Fe 0.35 Mn 0.45 Ni 0.05 Cu 0.05 Mg 0.05 Ti 0.05 O2.
3. The low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 1, characterized in that: The chemical formula is Na 0.63 Fe 0.39 Mn 0.45 Ni 0.04 Cu 0.04 Mg 0.04 Ti 0.04 O2 or Na 0.67 Fe 0.31 Mn 0.45 Ni 0.06 Cu 0.06 Mg 0.06 Ti 0.06 O2.
4. The method for preparing the low-cost and high-energy-density iron-manganese-based sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) weighing sodium carbonate, ferric oxide, manganese dioxide, nickel oxide, copper oxide, magnesium oxide and titanium dioxide according to the ratio of each element in the chemical formula to obtain raw material powders, mixing them evenly, and drying them to obtain a mixed powder; (2) The mixed powder obtained in step (1) is tableted, calcined, cooled to room temperature, and ground into powder to obtain a low-cost, high-energy iron-manganese-based sodium ion battery positive electrode material.
5. The method for preparing the low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 4, characterized in that: In step (1), ball milling is used for mixing, the ball milling medium is ethanol, the ball milling speed is 300-400 r / min, and the ball milling time is 4-6 h.
6. The method for preparing a low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 4, characterized in that: In step (1), drying is performed at 75-85°C.
7. The method for preparing a low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 4, characterized in that: In step (2), tableting is performed at 16-18 MPa.
8. The method for preparing a low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 4, characterized in that: In step (2), calcination is carried out at 900-1000° C. for 10-15 hours.
9. The method for preparing a low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to claim 4, characterized in that: The heating rate during calcination is 3-8°C / min.
10. Use of the low-cost and high-energy iron-manganese-based sodium ion battery positive electrode material according to any one of claims 1 to 3 in the preparation of sodium ion batteries.